2022
DOI: 10.3389/fimmu.2022.954798
|View full text |Cite
|
Sign up to set email alerts
|

Implications of regulatory T cells in non-lymphoid tissue physiology and pathophysiology

Abstract: Treg cells have been initially described as gatekeepers for the control of autoimmunity, as they can actively suppress the activity of other immune cells. However, their role goes beyond this as Treg cells further control immune responses during infections and tumor development. Furthermore, Treg cells can acquire additional properties for e.g., the control of tissue homeostasis. This is instructed by a specific differentiation program and the acquisition of effector properties unique to Treg cells in non-lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 212 publications
0
6
0
Order By: Relevance
“…Tregs are essential for the maintenance of self‐tolerance and immune homeostasis. They can cause the body to lose peripheral tolerance and lead to autoimmune diseases 35,36 . Although there is a consensus on the dysfunction of Tregs in SSc, the quantification of Tregs showed several paradoxical results, which may be related to heterogeneous factors of the studies, such as the enrolling phenotype of patients and the detection markers of Treg 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tregs are essential for the maintenance of self‐tolerance and immune homeostasis. They can cause the body to lose peripheral tolerance and lead to autoimmune diseases 35,36 . Although there is a consensus on the dysfunction of Tregs in SSc, the quantification of Tregs showed several paradoxical results, which may be related to heterogeneous factors of the studies, such as the enrolling phenotype of patients and the detection markers of Treg 32 .…”
Section: Discussionmentioning
confidence: 99%
“…They can cause the body to lose peripheral tolerance and lead to autoimmune diseases. 35,36 Although there is a consensus on the dysfunction of Tregs in SSc, the quantification of Tregs showed several paradoxical results, which may be related to heterogeneous factors of the studies, such as the enrolling phenotype of patients and the detection markers of Treg. 32 Interestingly, MacDonald et al 14 increased Tfh2 were found in the SSc group, with similar proportions of total Tfh, Tfh17, and activated Tfh with activation marker PD-1.…”
Section: F I G U R E 2 Altered Expression Of Cd4 +mentioning
confidence: 99%
“…Tregs are present within the non-lymphoid tissues, such as adipose tissue, muscle, and skin, and they are thought to play an important role in tissue homeostasis (39, 40). The inflamed lung tissues during allergic airway inflammation are heavily infiltrated with Tregs; however, the mechanisms through which they control lung inflammation has not thoroughly been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fatal systemic consequences with autoimmune events and multi-organ immune invasion and destruction upon mutation or deletion of Foxp3 , Treg cells are usually described as “guardians of peripheral immune tolerance”. In recent years, however, it has become evident that Treg cells can also be found in non-lymphoid tissues (NLTs), where they perform important homeostatic and regenerative functions ( 15 , 16 ). One prime example of a non-classical function of tissue Treg cells is from the visceral adipose tissue (VAT): In the murine system, local and systemic metabolic homeostasis has been linked to the presence and proper function of VAT-resident Treg cells, dependent on the interleukin (IL)-33 - ST2 axis, and tissue Treg cells expressing ST2 have also been found in the human system ( 17 19 ).…”
Section: Treg Cells Prevent Autoimmunity and Promote Tissue Regenerationmentioning
confidence: 99%